Autosomal recessive Stickler syndrome due to a loss of function mutation in the COL9A3 gene. - Faletra, Flavio; d'Adamo, Adamo P; Bruno, Irene; Athanasakis, Emmanouil; Biskup, Saskia; Esposito, Laura; Gasparini, Paolo (Am J Med Genet A, 2014)
Stickler syndrome (STL) is a clinically variable and genetically heterogeneous syndrome characterized by ophthalmic, articular, orofacial, and auditory manifestations. STL has been described with both autosomal dominant and recessive inheritance. The dominant form is caused by mutations of COL2A1 (STL 1, OMIM 108300), COL11A1 (STL 2, OMIM 604841), and COL11A2 (STL 3, OMIM 184840) genes, while recessive forms have been associated with mutations of COL9A1 (OMIM 120210) and COL9A2 (OMIM 120260) genes. Type IX collagen is a heterotrimeric molecule formed by three genetically distinct chains: α1, α2, and α3 encoded by the COL9A1, COL9A2, and COL9A3 genes. Up to this time, only heterozygous mutations of COL9A3 gene have been reported in human and related to: (1) multiple epiphyseal dysplasia type 3, (2) susceptibility to an intervertebral disc disease, and (3) hearing loss. Here, we describe the first autosomal recessive Stickler family due to loss of function mutations (c.1176_1198del, p.Gln393Cysfs*25) of COL9A3 gene. These findings extend further the role of collagen genes family in the disease pathogenesis.
Keywords: Adolescent; Arthritis; Bone and Bones; Child; Child, Preschool; Collagen Diseases; Collagen Type IX; Connective Tissue Diseases; DNA Mutational Analysis; Facies; Female; Genes, Recessive; Hearing Loss; Hearing Loss, Sensorineural; Homozygote; Humans; Male; Mutation; Pedigree; Retinal Detachment